1998
DOI: 10.2337/diabetes.47.12.1841
|View full text |Cite
|
Sign up to set email alerts
|

A novel insulin sensitizer acts as a coligand for peroxisome proliferator-activated receptor-alpha (PPAR-alpha) and PPAR-gamma: effect of PPAR-alpha activation on abnormal lipid metabolism in liver of Zucker fatty rats.

Abstract: We investigated the biological activity of a novel thiazolidinedione (TZD) derivative, KRP-297, and the molecular basis of this activity. When administered to obese Zucker fatty rats (obese rats) at 10 mg/kg for 2 weeks, KRP-297, unlike BRL-49,653, restored reduced lipid oxidation, that is, CO2 and ketone body production from [14C]palmitic acid, in the liver by 39% (P < 0.05) and 57% (P < 0.01), respectively. KRP-297 was also significantly more effective than BRL-49,653 in the inhibition of enhanced lipogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(136 citation statements)
references
References 0 publications
9
126
0
1
Order By: Relevance
“…Recently, some investigations have reported the effects of dual PPARa/g agonist in animal models of dyslipidemia and type 2 diabetes. [27][28][29][30][31] Our data are in good agreement with these reports, although in most of them, either no comparison was made with a specific PPARg agonist, or the dual agonist did not show a beneficial effect. The most striking result of the present study concerns the effect of Fenofibrate on body fat mass and body weight.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Recently, some investigations have reported the effects of dual PPARa/g agonist in animal models of dyslipidemia and type 2 diabetes. [27][28][29][30][31] Our data are in good agreement with these reports, although in most of them, either no comparison was made with a specific PPARg agonist, or the dual agonist did not show a beneficial effect. The most striking result of the present study concerns the effect of Fenofibrate on body fat mass and body weight.…”
Section: Discussionsupporting
confidence: 82%
“…As reported repeatedly, Rosiglitazone improves blood levels of glucose, insulin, triglycerides, NEFA and cholesterol. 7,27,29,31,34,35 On the other hand, Fenofibrate alone was, indeed, able to reduce serum lipid levels (TG, NEFA and cholesterol). 7,25,36 Surprisingly, it was also able to reduce significantly blood glucose concentration despite no effect on plasma insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination therapy of these medications is an attractive option for the treatment of obese type 2 diabetics (10,11). Compounds that have dual agonistic activity on both of these receptors have been shown to improve insulin sensitivity and dyslipidemia in obese diabetic animals (6,27). In the present study, we showed that isohumulones, the bitter compounds present in beer, activated PPARs ␣ and ␥ ameliorated insulin resistance and dyslipidemia in diabetic animals and reduced hyperglycemia in patients with type 2 diabetes.…”
Section: Isohumulones Up-regulated the Expression Of Genes Involved Isupporting
confidence: 51%
“…This differential behavior to dietary manipulations over time may be considered as a physiological adaptation of WAT to dietary fat excess. That is, sudden and short periods of dietary changes (fat elevation) down-regulate PPAR␥2 levels, perhaps to avoid an excess of new adipocyte appearance (38), while the maintenance of high-fat feeding over longer time periods modifies WAT, possibly via PPAR␥2-induced adipocyte differentiation (39).…”
Section: Fig 1 Ucp3 Ppar␥2mentioning
confidence: 99%